Disentangling carbon flow across microbial kingdoms in the rhizosphere of maize. (July 2019) - Hünninghaus, Maike; Dibbern, Dörte; Kramer, Susanne; Koller, Robert; Pausch, Johanna; Schloter-Hai, Brigitte; Urich, Tim; Kandeler, Ellen; Bonkowski, Michael; Lueders, Tillmann
Abstract: Numerous 13 CO2 labeling studies have traced the flow of carbon from fresh plant exudates into rhizosphere bacterial communities. However, the succession of the uptake of carbon leaving the roots by distinct rhizosphere microbiota has rarely been resolved between microbial kingdoms. This can provide valuable insights on the niche partitioning of primary rhizodeposit consumption, as well as on community interactions in plant-derived carbon flows in soil. Here, we have traced the flow of fresh plant assimilates to rhizosphere microbiota of maize ( Zea mays L.) by rRNA-stable isotope probing (SIP). Carbon flows involving bacteria, unicellular fungi, as well as protists were observed over 5 and 8 days. Surprisingly, labeling of Paraglomerales and several bacteria including Opitutus, Mucliaginibacter and Massilia spp. was especially apparent in soil surrounding the strict rhizosphere after 5 d. This highlights the central role of arbuscular mycorrhizal fungi (AMF) as a shunt for fresh plant assimilates to soil microbes not directly influenced by root exudation. Distinct trophic webs involving different flagellates, amoeba and ciliates were also observed in rhizosphere and surrounding soil, while labeling of filamentous saprotrophic Ascomycota or Basidiomycota was not apparent. This challenges the proposed "sapro-rhizosphere" concept and demonstrates the utility of rRNA-SIP to disentangle inter-kingdom microbial relationships in the rhizosphere. Graphical abstract: Image 1 Highlights: rRNA-SIP was used to trace plant-derived carbon flows in the rhizosphere of maize. 13 C-labeling of mycorrhiza was stronger in surrounding soil than in the rhizosphere. Labelling of bacteria incl. Opitutus spp. was also stronger in surrounding soil. AMF are a shunt of plant assimilates to microbes outside the strict rhizosphere.